Pola Komunikasi Gender dalam Politik - Sari Ekowati; Deby Puspitaningrum (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study focuses on gender communication patterns in politics. The aim of this study is to analyze gender communication patterns, which are considered to still experience inequality in politics. The differences in communication styles depend on where he comes from, where he was born, his educational background, his age, and his gender. Whether we realize it or not, gender inequality occurs not only in society but also in the media as a gender constructor. Various gender injustices have occurred since the 19th century and are trying to break down patriarchal culture. Indonesia has a patriarchal culture that is still rooted, although it is slowly starting to erode due to the development of the modernization era. Women are now starting to dare to express their opinions in public spaces, such as in the political arena. But again and again, bitter pills always seem to be the daily intake of Indonesian women. Gender inequality is also felt by women who enter the world of politics. The incessant feminist movement has not changed the construction of women by the media. Gender inequality that occurs should be minimized with good gender-sensitive communication, without forgetting equality.